(untitled) (Journal of Computational Mathematics, 2005)
In this paper, we present an algorithm for the CDT subproblem. This problem stems from computing a trust region step of an algorithm, which was first proposed by Celis, Dennis and Tapia for equality constrained optimization. Our algorithm considers general case of the CDT subproblem, and convergence of the algorithm is proved. Numerical examples are also provided.